2021
DOI: 10.1111/aab.12680
|View full text |Cite
|
Sign up to set email alerts
|

On the use of tree‐ring area as a predictor of biomass accumulation and its climatic determinants of coffee tree growth

Abstract: The use of growth rings dimensional parameters has been an important tool for the understanding of growth, biomass allocation and climatic characterisation of forest species. However, its potential is unknown in perennial crops of socio‐economic importance, such as coffee. This work aimed to understand how the analysis of the growth rings can be used as a proxy to understand the climatic determinants of vegetative growth and biomass allocation in the different organs of coffee trees. The work was carried out i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…On the other hand, considering the negative correlation between δ 13 C values and water availability (Codron et al, 2005; Ma et al, 2012; Stewart et al, 1995; Vitória et al, 2018), δ 13 C values follow the region's precipitation dynamics (data not shown in this document, but reported in Toro‐Herrera et al, 2020). 2012/2013 and 2013/2014 periods (H1 and H2) presented average annual rainfall of up to 400 mm below 2014/2015.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…On the other hand, considering the negative correlation between δ 13 C values and water availability (Codron et al, 2005; Ma et al, 2012; Stewart et al, 1995; Vitória et al, 2018), δ 13 C values follow the region's precipitation dynamics (data not shown in this document, but reported in Toro‐Herrera et al, 2020). 2012/2013 and 2013/2014 periods (H1 and H2) presented average annual rainfall of up to 400 mm below 2014/2015.…”
Section: Discussionsupporting
confidence: 59%
“…From the process of normalization of time series obtained from the area of the growth ring reported by Toro‐Herrera et al (2020), it was seen that there was a trend of rapid growth in the first years of the tree and later a stabilization in the following years until the date of collection. Thus, the 2012/2013 period had the highest growth rate, while the 2014/2015 period had the lowest rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations